The ERAD network - Hebert, Daniel (Henry Stewart Talks, 2012)
Eukaryotic secretory pathway, ER processes, ERAD steps, Substrate recognition, Glycans as sorting signals, Yeast ERAD process, Mammalian ERAD process, ERAD adapter proteins, ERAD translocons, ERAD E3 ligases